Rehabilitating Critical Land in the Watersheds of North Sulawesi Province, Indonesian: Strategies and Community-Based Implementation - Fabiola Saroinsong; Jonathan Muntu (Asia Pacific Journal of Interdisciplinary Studies, 2025)
Abstrak:  The degradation of watersheds (DAS) due to critical land is a primary environmental challenge in North Sulawesi, Indonesia, leading to increased flooding, erosion, sedimentation, and disruption of water resources. This study aims to describe the strategy and implementation of Forest and Land Rehabilitation (RHL) programs in the province, with a focus on the priority Tondano Watershed. Using a descriptive qualitative methodology based on secondary data from government reports and relevant literature, this research outlines the comprehensive framework for RHL, from long-term planning (RURHL-DAS) to annual operational plans (RTnRHL). Key activities include professional seedling procurement, extensive community socialization, and on-ground rehabilitation through community forests (hutan rakyat). Implementation data for 2024-2025 shows the rehabilitation of 217.12 hectares, combining seedling provision (37.12 ha) and community forests (180 ha). The findings highlight that a synergistic approach, integrating ecological restoration with socio-economic benefits through agroforestry and community empowerment, is crucial for the success and sustainability of rehabilitation efforts. The study concludes that effective RHL in North Sulawesi requires strong cross-sectoral coordination, systematic planning, and active local community involvement to restore ecological functions and enhance community resilience. .